EVALUASI PELAKSANAAN PROGRAM KEBIJAKAN PELAYANAN OBSTETRI NEONATAL EMERGENSI KOMPREHENSIF (PONEK) DI RSUD MAJENE KABUPATEN MAJENE - Muh Fauzar Al-hijrah; Muhammad Irwan; Muhammad Hosni Mubarak (Bina Generasi : Jurnal Kesehatan, 2023)
Background Maternal and infant mortality rates are still a major regional government's homework, especially for major health workers. In accordance with December 2016 data, the infant mortality rate is 62 people and the mother is 8 people. Maternal mortality cases in Majene Regency in 2018 experienced a significant increase. The amount reaches up to 50 percent. The purpose of this study was to evaluate the implementation of the policy program of the compherensive emergency neonatal obstetric sarvices (CENOS) at Majene General Hospital based on inputs, processes and outputs. MethodeThe research was descriptive in character with the phenomenological approach using triangulation techniques. The total samples comprised 18 person as the informants. The data collection used the techniques of observation, interviews, and documentation. The data were analyzed using qualitative analysis. The research results revealed that at the input stage the availability of the health workers was still inadequate according to the standard number of CENOS force-only 16 of the 29 were available. As for the facilities, the rooms, beds, and WC were still inadequate. Besides, same of the CENOS technical equipments, such as the minimum pipes, injection instruments, and electric pumps were not yet available. Even the opportunities for the CENOS workers to join the CENOS training were still minimum. However, at the process stage, the emergency services carried out to the mother and baby were less than 30 minutes. Also, the CENOS implementation had always used the manual of the CENOS SOP of Majene Local General Hospital as reference. As for the constraints faced in implementing the CENOS SOP were the lacks of the supporting facilities of CENOS program. At the output stage, it was found that MMR and IMR had decreased, though there were still some of the community members preferred to give birth with the shamans rather than in hospitals. The conclusion of this study shows that the CENOS services in the hospital are not optimal due to the constraints of PONEK skills and facilities